Art, literature, and passions of the skies - Tymieniecka, Anna Teresa (Analecta Husserliana, The Yearbook of Phenomenological Research, 2012)
Flashes of lightning, resounding thunder, gloomy fog, brilliant sunshine...these are the life manifestations of the skies.  The concrete visceral experiences that living under those skies stir within us are the ground for individual impulses, emotions, sentiments that in their interaction generate their own ever-changing clouds.      While our intellect concentrates on the discovery of our cosmic position, on the architecture of the universe, our imagination is informed by the gloomy vapors, the glimmers of fleeting light, and the glory of the skies.      Reconnoitering from the soil of human life and striving towards the infinite, the elan of imagination gets caught up in the clouds of the skies.  There in that dimness, sensory receptivity, dispositions, emotions, passionate strivings, yearnings, elevations gather and propagate.      From the "Passions of the Skies" spring innermost intuitions that nourish literature and the arts.